Spatial-time variation by Built-up and NDBI indices of the municipalities of Maringá and Sarandi/PR: comparison between the years 2013 – 2020 - Uema, Diogo Yukio; Eduvirgem, Renan Valério (Revista Nacional de Gerenciamento de Cidades, 2021)
This work aims to use the Normalized Difference Built-up Land Index and Built-up Index to evaluate the urban perimeters of Maringá and Sarandi, Paraná. In order to identify if there was a spatial difference in the built areas. The methodological procedures were based on the spatial analysis of urban perimeters, generation of each index, interaction between index and environment. In the results and discussions, the values obtained by the indexes are approached and the localities with higher and lower values are scored, with possible causes denoted, as well as the relationship with the literature. It was concluded that Maringá and Sarandi, Paraná, have urban density in an advanced stage of urban consolidation, in the perspective of soil waterproofing, since the indexes worked do not measure vertical densities, but horizontal ones.